EFISIENSI EKSEKUSI JAMINAAN FIDUCIA PASCA PUTUSAAN MK NO: 18/PUU-XVIII/2019 TERHADAB PERUSHAAN PEMBIAYAAN (MULTI FINANCE) - Pinto Utomo; Budiarsih Budiarsih; Evi Konggres (Fakultas Hukum Universitas Muhammadiyah Palu, 2020)
Decicion of the Constitotional Courst nomber 18/PUUU-VXIII / 2019 annulls some of the phrases and their explanations contained in article 15 paragraph (2) along with their explanations and faragraph (3) of the fiduusiary Acts contrary to thee 1945 Constitution as long it is not edited as interpreted by thi Panel off Judges off the Court Thee Constitution contained in the related decision. The implementation of fiduciary guarantee execution is no longer as effective and as efficient as before. This paper focuses on how efficient is the implementation of Fiduciary Guarantee after the Decision of Mk No: 18 / PUU-XVII / 2019 towards Financing Companies. The normative juridical method for reviewing written legislation and legal principles by examining the rules of legal norms. The results of the study found that fiduciary guarantees still have or are attached to an executorial power whose decisions are the same as court decisions that have legal power permanent, and thi creditur as the recipent of fidusiaary retains full authority tu be able to carry out his own execution (parate execution), as long as the debtor has